2014
DOI: 10.1002/prep.201300058
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Silicon Powder Characteristics on the Combustion of Silicon/Teflon/Viton Nanoenergetics

Abstract: Due to its thin passivation layer, potentially good aging characteristics, and ease of surface functionalization nanoscale silicon (Si) may offer some advantages over nanoaluminum as a reactive fuel in nanoenergetic compositions, particularly with fluorine‐based oxidizers. Currently, Si nanopowder can be quite expensive and the quality of commercial powders has been found to vary drastically. As a result limited efforts have focused on the role of specific surface area, active content, morphology, and dominant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
7
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 34 publications
0
7
0
1
Order By: Relevance
“…Si also has a thinner native oxide layer of 1–3 nm than Al, and it is resistant to electrostatic discharge. Importantly, the surface of Si can be easily functionalized, , facilitating the use of coating and surface modification to tailor its ignition and burning properties. Several previous studies have shown that Si-based thermites have comparable combustion properties as Al-based thermites, ,, in terms of adiabatic combustion temperatures (∼3000 K) and burning rates (40–530 m/s) .…”
Section: Introductionmentioning
confidence: 99%
“…Si also has a thinner native oxide layer of 1–3 nm than Al, and it is resistant to electrostatic discharge. Importantly, the surface of Si can be easily functionalized, , facilitating the use of coating and surface modification to tailor its ignition and burning properties. Several previous studies have shown that Si-based thermites have comparable combustion properties as Al-based thermites, ,, in terms of adiabatic combustion temperatures (∼3000 K) and burning rates (40–530 m/s) .…”
Section: Introductionmentioning
confidence: 99%
“…Si + C 2 F 4 (c) / SiF 4 + 2C DH Ө ¼ À6.21 kJ g À1 (1) systematically investigated the roles of specic surface area, active content, morphology, and particle size of the Si powder on the combustion behaviour of Si/PTFE/Viton nanoenergetic composites. 17 However, powder-mixing technique was used in these studies to prepare nanoenergetic composites, and hence the interfacial contact and distribution of fuel and oxidizer are rather random. As one kind of nanostructured energetic composites, nano-porous Si-based nanoenergetics attract much more attention.…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have investigated the combustion properties of Si particles with solid oxidizers (e.g., sodium perchlorate and fluorinated compounds), including flame propagation speeds and pressurization rates, 9−11 and found that more intense burning and faster flame propagation are achieved when the size of Si particles decreases from microns to nanometers. 11 One study looked into the ignition properties of micron-sized Si particles in air by electric spark ignition 12 and found that the minimum ignition energy decreased from 2.9 J for 18 μm Si particles to around 0.06 J for 3.6 μm Si particles. Other studies have investigated the ignition properties of porous Si (P−Si), which is crystalline Si containing nanosized pores with hydrogen terminated surfaces.…”
mentioning
confidence: 99%
“…Such requirements call for understanding and quantification of the ignition and combustion properties of Si particles. Some studies have investigated the combustion properties of Si particles with solid oxidizers (e.g., sodium perchlorate and fluorinated compounds), including flame propagation speeds and pressurization rates, and found that more intense burning and faster flame propagation are achieved when the size of Si particles decreases from microns to nanometers . One study looked into the ignition properties of micron-sized Si particles in air by electric spark ignition and found that the minimum ignition energy decreased from 2.9 J for 18 μm Si particles to around 0.06 J for 3.6 μm Si particles.…”
mentioning
confidence: 99%